STEAM-BASED LEARNING TO ENHANCE TECHNOLOGY AND INNOVATION SKILLS OF ELEMENTARY SCHOOL STUDENTS - AmirUniversitas Negeri Makassar , Nour Ariyanti; Sahabuddin, Romansyah; Irfan, Muhammad; Lutfi, Lutfi; Wajdi, Muhammad (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to explore how the application of STEAM-based learning can improve technology and innovation skills in primary school students. The issue raised is the need to understand the effectiveness of STEAM methods in improving students' ability to face modern technological challenges. The writing of this article uses a systematic review method based on several references in the form of books and scientific publication articles from various open source library sources. The results of this study show that students are not only better able to use technology, but also show improvements in creativity and critical thinking skills. These findings are of great significance as technology and innovation skills instilled at an early age become the foundation for the development of higher competencies at an advanced level which is crucial in the field of education. This study therefore provides important insights into the integration of STEAM learning in the primary education curriculum and its long-term implications for improving the quality of human capital.